The Late Antique "Palace" in Polače Bay (Mljet) - Tetrarchic "Palace"? - Turković, Tin (2011)
Central building of the spatious late antique complex situated in in Polače bay on the island Mljet (Croatia) has been subject of numerous studies. However, none of them offered definite conclusions about the datation of this monumental late antique edifice situated in midst of an elaborated architectural complex. In the article a new datation and interpretation of the central building of the complex is proposed, based on a formal and historical analysis.
Projekt MZOS
ENG